Kierkegaard on the Philosophy of History - Patios, G. author. aut Link
XI, 187 p.
Keywords: History doesn't have to mean only an effort to know the past. It can be instead, according to Kierkegaard, a willful and personal choice regarding the creation of the future. Kierkegaard offers us an amazing new approach to the problem of what is history and who makes it.